PD‐1/PD‐L1 pathway: Basic biology and role in cancer immunotherapy - Salmaninejad, Arash; Valilou, Saeed Farajzadeh; Shabgah, Arezoo Gowhari; Aslani, Saeed; Alimardani, Malihe; Pasdar, Alireza; Sahebkar, Amirhossein (Journal of cellular physiology, 2019)
Over the course of past few years, cancer immunotherapy has been accompanied with promising results. However, preliminary investigations with respect to immunotherapy concentrated mostly on targeting the immune checkpoints, nowadays, emerge as the most efficient strategy to raise beneficial antitumor immune responses. Programmed cell death protein 1 (PD‐1) plays an important role in subsiding immune responses and promoting self‐tolerance through suppressing the activity of T cells and promoting differentiation of regulatory T cells. PD‐1 is considered as an immune checkpoint and protects against autoimmune responses through both induction of apoptosis in antigen‐specific T cells and inhibiting apoptosis in regulatory T cells. Several clinical trials exerting PD‐1 monoclonal antibodies as well as other immune‐checkpoint blockades have had prosperous outcomes and opened new horizons in tumor immunotherapy. Nonetheless, a bulk of patients have failed to respond to these newly emerging immune‐based approach and the survival rate was not satisfying. Additional strategies, especially combination therapies, has been initiated and been further promising. Attempts to identify novel and well‐suited predictive biomarkers are also sensed. In this review, the promotion of cancer immunotherapy targeting PD‐1 immunoinhibitory pathway is discussed. In this review, the promotion of cancer immunotherapy targeting programmed cell death protein 1 immunoinhibitory pathway is discussed.